Analisis Penerapan Senam Irama Berbasis Kearifan Lokal - Nurmalinda Zari; Fitria Rizka (Prosiding Temu Ilmiah Nasional Guru, 2022)
This study aims to find out how to apply rhythmic gymnastics based on local wisdom to children in TK A PAUD Al Mizan II Ampelu Village. The research method used is a qualitative research described descriptively involving 20 students and teachers as a learning model. Data collection techniques used are observation, interview and documentation techniques. While the analysis technique includes data collection, data reduction, data presentation which is carried out in descriptive form. The results showed that the application of rhythmic gymnastics based on local wisdom to children in PAUD Al-Mizan could be done well, then there was progress in children becoming more focused in learning gymnastics and being able to follow gymnastics activities well. From the results of the research that has been done, it can be concluded that the application of rhythmic gymnastics based on local wisdom in early childhood can be implemented in accordance with the PAUD curriculum and is proven to improve skills of early childhood in PAUD Al Mizan, Ampelu Village.